Body-size regulation: combining genetics and physiology. - Shingleton, A.W. (Current Biology, 2005)
New research has revealed that the activity of the insulin-signaling pathway in the prothoracic gland of Drosophila modulates ecdysone release and thereby influences both the duration and rate of larval growth.